Selection and characterization of DNA aptamer against glucagon receptor by cell-SELEX - Guodong Wang (Nature Portfolio, 2017)
Abstract Excessive secretion of glucagon, a functional insulin antagonist, significantly contributes to hyperglycemia. Glucagon exerts its physiological functions through activation of the glucagon receptor (GCGR). Inhibition of GCGR activity represents a potential therapeutic approach for reducing excess glucose production in diabetes mellitus. Aptamers are short DNA or RNA oligonucleotides evolved from systematic evolution of ligands by exponential enrichment (SELEX). Here, we have successfully selected a DNA aptamer against GCGR by cell-SELEX, which can specifically bind membrane protein of CHO-GCGR cells with a K d of 52.7 ± 5.1 nM. Aptamer-mediated pull-down and gcgr knockdown assay verified that GCGR was the target of aptamer GR-3. Binding analysis revealed that GR-3 could recognize other cells with different affinity according to the level of GCGR protein expressed in these cells. Hepatic tissue imaging suggested that GR-3 could bind the cell membrane of hepatic tissues. With the advantages of small size, high binding affinity, good stability, lack of immunogenicity, and easy synthesis, aptamer GR-3 against GCGR can be a promising tool with the potential to attenuate hyperglycemia in diabetes mellitus.